Herping: Natural Exploration as Bioeducation of Herpetofauna Animal Diversity - Meylani, Vita; Hernawati, Diana (Future Science / FSH-PH Publications, 2022)
Learning biology is about theory and practice while in the laboratory or environment. Animalia is one of the focuses of Biology and one of the topics that could not practice in the laboratory but should practice in the environment. Learning in an environment would give students any experiences. This study aims to report a case study that explores the experiences of prospective teacher students about learning outdoors through a herping activity. This research was taken from a university in Indonesia from June until December 2019. Data retrieval is taken through semi-structured interviews. Data analysis used the phenomenological design of 22 participants to be interviewed. The findings reveal that the challenges found in the field include field mastery, unpredictable weather, and finding the correct object. However, natural phenomena that are open in the wild become an attraction as bio-education develops for prospective teacher students. Understanding science material and science epistemological abilities is likened to a combination of hands-on activities students become complete with minds-on practices. For this reason, it is crucial when the learning process is packaged in frames that can stimulate prospective teacher students to be more active. The findings are how to combine formal learning in the classroom with wild herping activities to develop student bio-education.